The effectiveness of family planning counseling on the selection of contaceptives in north tolo village kelara district jeneponto regency - Ningsi, Agustina; Gasma, Asmawati; Veronika, Windi (Politeknik Kesehatan Makassar, 2022)
Family planning counseling is very important to provide information as a source of knowledge. With family planning counseling, couples of childbearing age can gain good and useful knowledge so that knowledge can affect motivation in decision making.The purpose of this researchis to find out the effect of the effectiveness of family planning counseling on the selection of contraceptives for couples of childbearing age.The research design used in this study was the Pree experiment. The population in this study were 58 couples of childbearing age and the number of samples in this study were 19 couples of childbearing age with a sampling technique that was simple random sampling. The analysis used in this study was the Paired Sample T-Test.The results showed that door-to-door family planning counseling contributed to the decision to choose one contraceptive method for couples of childbearing age in the North Tolo area. Keywords : Family Planning Counseling, Decision Making